MiR‐296 inhibits proliferation and induces apoptosis by targeting FGFR1 in human hepatocellular carcinoma. Issue 23 (21st October 2016) - Wang, Liyan; Bo, Xiaotong; Zheng, Qinghua; Xiao, Xuhua; Wu, Linling; Li, Bin
Abstract : MiR‐296 was previously reported to be underexpressed in hepatocellular carcinoma (HCC). However, the clinical value of miR‐296 and its function in HCC remain poorly understood. In this study, we found that miR‐296 levels are decreased in HCC specimens and cells, and that the underexpression of miR‐296 is associated with adverse clinical parameters and poor overall survival rate. In vitro experiments indicate that miR‐296 inhibits proliferation, colony formation, and cell cycle progression, and enhances apoptosis in HCC cells. Notably, we found that the fibroblast growth factor receptor 1 (FGFR1) is a downstream target that mediates the functions of miR‐296 in HCC. Thus, our findings indicate that miR‐296 exerts a tumor suppressive role in HCC and is a potential biomarker and drug‐target. Abstract :